The Relationship Between Breakfast Habits and Learning Concentration in Students at SMP Negeri 8 Manado - Latara, Nurmifta; Adam, Hilman; Maino, Irny E. (Science Tech Group, 2026)
Breakfast is an essential meal that provides energy to support daily activities and cognitive functions, particularly learning concentration among school-aged children. Adequate breakfast consumption contributes to improved nutritional status, which is closely aligned with Sustainable Development Goal (SDG) 2, aimed at ending hunger and improving nutrition. Furthermore, optimal nutrition supports cognitive development and learning capacity, which are fundamental to achieving SDG 4, ensuring inclusive and equitable quality education. In Indonesia, a substantial proportion of students skip breakfast, a behavior that may negatively affect their ability to concentrate, think clearly, and maintain physical endurance during school activities. This study aimed to examine the relationship between breakfast habits and learning concentration among students at SMP Negeri 8 Manado. The study employed a quantitative analytic survey design with a cross-sectional approach. A total of 85 students were selected using proportional random sampling. Data were collected through structured questionnaires to assess breakfast habits and concentration test sheets to measure learning concentration. Statistical analysis was conducted using the Spearman Rank correlation test. The findings revealed that more than half of the students had good breakfast habits (52.9%), while only 29.4% demonstrated good learning concentration. Statistical analysis showed a significant relationship between breakfast habits and learning concentration (p = 0.007 < 0.05), with a moderate strength of correlation (r = 0.292). The study concludes that there is a positive and significant relationship between breakfast habits and learning concentration among students at SMP Negeri 8 Manado. Regular and adequate breakfast consumption plays an important role in supporting students’ concentration during learning activities, highlighting its contribution to nutritional well-being and educational quality in line with the SDGs.